School Accreditation Strategy: Academic Policy and Integrative Supervision Model - Radhiyah; Prasetyo, Muhammad Anggung Manumanoso (Universitas Pendidikan Ganesha, 2024)
Suboptimal follow-up of supervision due to minimal reports on learning developments This study aims to analyze school accreditation strategies: academic policies and integrative supervision models. This study uses a qualitative paradigm of case study techniques. Data collection uses observation, interview and documentation review techniques. Data analysis is done through data condensation, data presentation, and conclusion. Informants consist of the principal as a policy maker, senior teachers and accreditation coordinators. The study results show that the implementation of supervision is carried out through the stages of planning, implementation, reflection, evaluation, and follow-up of supervision. Planning activities include forming a supervision team, determining the date of implementation and supervision techniques. The implementation of supervision is carried out through direct observation and analysis of the results of school accreditation. The accreditation strategy begins through the principal's effectiveness and reflects the results of supervision. The study results reveal that the integrative supervision model includes academic, clinical, and transformative supervision. Follow-up supervision through collaborative leadership of the principal involves school residents and the community in making policy directions for improving the learning process through academic supervision as a supporting factor in achieving superior accreditation results. The research has social implications regarding changes in the paradigm of policy managers, such as the fact that accreditation policy is a form of quality assurance that must be achieved seriously by improving educational services, not as an incident or formality.